EXPLORATORY SURVEY ALONG THE SOUTH-WEST COAST OF INDIA WITH REFERENCE TO THE USE OF TRY-NET - Mathew, K J; Nair, A K Kesavan (Indian Journal of Fisheries, 2011)
The results of an exploratory survey for the assessment of prawn resources conducted along the south-west coast of India for a short period in 1967 are presented. The trend in total catch as well as prawn catch showed a decrease from the beginning to the end of the survey. During the survey, besides two trawl nets, a small try-net was aslo used for testing the grounds. A non-parametric test was applied to the catches by the two types of nets, the trawl net and the try-net, and it was found that the catch efficiency of the nets was the same. The possibility of using such a try-net for exploratory surveys and also for testing the grounds during commercial trawling is discussed.